Hukuksal Geçerlilik Bakımından Resmi Belgelerin Biçimsel Özellikleri - (:unkn) unknown (My University, 2007)
Kurumlarda idari usul ve işlemler çerçevesinde bir yetkili tarafından üretilen belge, aynı zamanda ait olduğu türün karakteristik yapısına göre belirli biçimsel özelliklere sahip olmalıdır. Bu özellikler, birbiriyle uyumlu olmalı, belge profilinde doğru yerde verilmeli, belgenin aidiyetinin ve kurumsal ilişkisinin belirlenmesinde ipuçları sağlamalıdır. Bu çalışmada hukuksal geçerlilik açısından resmi belgenin biçimsel özellikleri ele alınmıştır. Makalenin amacı, idari bir işlemin delili olan belgeler, hukuki bakımdan analiz edilirken imza, mühür, sayı ve antet gibi özelliklerin nasıl kullanılabileceğini göstermektir. Elde edilen sonuçlar, elektronik belgelerin güvenilirliği incelenirken de kullanılabilir.

Documents created by authorized persons in institutions compliant with administrative procedures and processes, should, at the same time, possess certain physical features of the category to which they belong. These features should be consistent with each other and should be placed in the appropriate places in the document profile, thus providing the user with clues about when and by which governmental body the document is issued. This study discusses physical characteristics of public records regarding legal admissibility. The study attempts to describe how physical features such as signature, seal, number and heading can be used, while determining the legal admissibility of documents as evidences of administrative transactions. The findings of the study can also be used to establish the authenticity of electronically transmitted messages.
Physical Features of Public Records Regarding the Legal Admissibility
Keywords: Kamu Yönetimi